Islamic on Screen: Religious Narrative on Indonesia's Television - Fauzy, Fahmi Imam; Jannah, Aptiani Nur (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2021)
The digital era does not necessarily replace television as a source of information, including about religion. Television remains vital in the construction and dissemination of religious information in Indonesian society. The survey conducted by PPIM in 2018 shows that 33.73% of Generation Z (youth) access television as a source of religious knowledge (Saputra 2018). The previous research by Alvara in 2020 also found that 54.2% of respondents listen to and watch religious sermons from television (Alvara 2020). Therefore, PPIM UIN Syarif Hidayatullah Jakarta through Media and Religious Trend In Indonesia (MERIT) conducted a research entitled “Preaching on Screen: Television and Religious Narrative in Indonesia”, which ran from July to December 2020. The research found that moderate and conservative of islam are highly dominating on television programs in Indonesia.This research is also driven by the significance of television in disseminating religious knowledge demonstrated by the widespread proliferation of religious programs produced on television. These religious programs are broadcasted not only during Ramadan month but also on daily basis. The significant role of television as a source of religious knowledge is also illustrated by the high public interest in watching religious programs. For example, the